THE ROLE OF HUMAN RESILIENCE EFFORTS TOWARD A COMPETITIVE TOURISM DESTINATION IN THE CITY OF SEMARANG - CENTRAL JAVA: THE ROLE OF HUMAN RESILIENCE EFFORTS TOWARD A COMPETITIVE TOURISM DESTINATION IN THE CITY OF SEMARANG - CENTRAL JAVA - Irhamni, Muhammad Ricza; Lase, Jayadi (International Journal of Management, Business, and Social Sciences, 2024)
This article examines the role of human resources (HR) in building resilience and competitiveness of tourist destinations in Semarang City. Tourism is important in improving the regional economy, but it faces global challenges, including changes in tourism trends and the pandemic. This research highlights the importance of developing and training competent HR to address these challenges. Using a qualitative approach, the study identifies the role of HR in supporting the sustainability of tourist destinations through innovation, technology, and collaboration among stakeholders. The results show that improving HR quality, effective leadership, and digital technology are key factors in strengthening the competitiveness of Semarang's tourist destinations at national and international levels.